PREFERENSI MUZAKKI TERHADAP ZAKAT ONLINE DI ERA DIGITAL: ANALISIS PENGARUH FAKTOR SOSIAL, BUDAYA, DAN PRIBADI DI INDONESIA - Yaniar Dwi Fitriani (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2026)
The high poverty line in Indonesia and the majority of the Muslim community make zakat one of the potentials to reduce poverty. Zakat is a social activity to help ease the government in reducing poverty but not to eradicate poverty. Technological advances can be used to pay zakat on the grounds of helping efficiency for paying zakat online to maximize the potential of zakat in this new era with technology. Even so, the community still does not fully trust organizations or zakat collection platforms in paying zakat online. So this study examines the preferences of the community in paying zakat, whether muzakki prefers to pay zakat online or prefers the traditional method directly given to mustahik. The analysis method of this study uses a quantitative approach and descriptive analysis with binary logistic regression analysis testing. The main purpose of writing this study is to analyze and examine the influence of social factors, cultural factors, and personal factors that influence muzakki's preferences in paying zakat online. The sample with the special characteristics of a Muslim, over 17 years old, having used an online zakat platform, and residing in Indonesia as many as 70 respondents. The results of this study are the prediction of muzakki's preference for choosing to pay zakat online by 75.7% out of 100%. The preference of muzakki to pay zakat online in Indonesia is influenced by social factors, which have a positive and significant effect, meaning that every muzakki who pays zakat online increases the desire or preference of muzakki in paying zakat online by 28.5 times. The preference of muzakki to pay zakat online in Indonesia is not influenced by cultural factors because the results are not significant even though the direction is positive. The preference of muzakki to pay zakat online in Indonesia is influenced by personal factors, which have a negative and significant effect, meaning that every muzakki who pays zakat online decreases the desire or preference of muzakki in paying zakat online by 0.273 times.